2002
DOI: 10.1590/s1415-47572002000100004
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of polymorphisms at the HSA alpha1-acid glycoprotein (ORM*) gene locus in Caucasians

Abstract: Human α 1 -acid glycoprotein (AGP) or orosomucoid (ORM) is a major acute phase protein that is thought to play a crucial role in maintaining homeostasis. Human AGP is the product of a cluster of at least two adjacent genes located on HSA chromosome 9. Using a range of restriction endonucleases we have investigated DNA variation at the locus encoding the AGP genes in a panel of healthy Caucasians. Polymorphisms were identified using BamHI, EcoRI, BglII, PvuII, HindIII, TaqI and MspI. Non-random associations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(28 reference statements)
0
5
0
Order By: Relevance
“… 16 Levels of AAG may be affected by a number of environmental factors 17 and there are polymorphisms that show differences in AAG allele frequencies between ethnic groups. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 Levels of AAG may be affected by a number of environmental factors 17 and there are polymorphisms that show differences in AAG allele frequencies between ethnic groups. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al, (1990) showed that there was a higher unbound fraction of disopyramide, propranolol, and diphenhydramine in Chinese patients ( n = 8) compared to White patients ( n = 8) and they attributed this to lower levels of AAG in the Chinese 16 . Levels of AAG may be affected by a number of environmental factors 17 and there are polymorphisms that show differences in AAG allele frequencies between ethnic groups 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…Although the variants of this glycoprotein have been previously defined using electrophoretic characteristics (Weidinger et al, 1987;Nevo et al, 1996;Yuasa et al, 1997;Owczarek et al, 2002;Yuasa et al, 2006), the recent application of gene-specific PCR and sequencing methods has provided the possibility to distinguish the genetic heterogeneity of ORM1.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rearrangement of the ORM1 and ORM2 genes was not specifically evaluated in our population, because it was not the main objective of this study, several interesting results have been recently described. The frequencies of duplicated or triplicate genes encoding ORM1 and ORM2 proteins, together with the appearance of different gene arrangements, may distinguish some populations, in terms of their ORM diversity (Nakamura et al, 2000;Owczarek et al, 2002;Yuasa et al, 2006). For example, the duplication of ORM1 gene is frequent in Africans and Japanese (high as 10-20%) (Nakamura et al, 2000;Yuasa et al, 2006), and other studies dealing with European and Australian populations suggest that the increase in gene numbers may occur at appreciable frequencies (Dente et al, 1987;Rocha et al, 1993;Owczarek et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…AGP is highly polymorphic, and more than 70 AGP variations in the serum have been identified by isoelectric focusing methods 8 . ORM genetic variations, mainly focusing on the exon regions, have been investigated in several ethnic populations, and ethnic differences were recognized 9–13. Duplications or null variations of ORM genes have been also detected in several populations, and the frequency of ORM1 duplication in Japanese subjects was reported to be approximately 20%, although null variations of ORM genes were very rare 8,14,15.…”
Section: Introductionmentioning
confidence: 99%